2003
DOI: 10.1007/s10311-002-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polycaprolactone by microwave irradiation ? an interesting route to synthesize this polymer via green chemistry

Abstract: Poly(ε-caprolactone) has become an important biocompatible and biodegradable polymer. Indeed, due to its multiple biomedical applications, the synthesis of polycaprolactone has received increased attention in the past few decades. Moreover, microwave irradiation is a very clean modern technique widely used for green chemistry. Here, several polymers were synthesized by microwave irradiation, without any solvent, using nontoxic, biologically acceptable lanthanide halides as initiators. Reaction times varied bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Two different microwave equipments were employed: a monomodal Prolabo Synthwave S402 equipped with an IR temperature sensor (15 to 45 min of irradiation at 180 -200 °C) and a Sairem GMP 12T provided with a Marconi F1192-12 water-cooled circulator (3 to 20 min of irradiation at 230 °C). Interestingly, the degradation rate of PCL was also assessed: it was found that the slow hydrolytic process is accelerated by the catalyst, while the faster enzymatic process is inhibited (Barbier-Baudry et al, 2003). The Sn(Oct) 2 catalyzed microwave assisted polymerization of ε-caprolactone ( -CL) can be initiated by methacrylic acid or acrylic acid yielding radical polymerizable PCL macromonomers.…”
Section: Poly(ε-caprolactone)mentioning
confidence: 99%
“…Two different microwave equipments were employed: a monomodal Prolabo Synthwave S402 equipped with an IR temperature sensor (15 to 45 min of irradiation at 180 -200 °C) and a Sairem GMP 12T provided with a Marconi F1192-12 water-cooled circulator (3 to 20 min of irradiation at 230 °C). Interestingly, the degradation rate of PCL was also assessed: it was found that the slow hydrolytic process is accelerated by the catalyst, while the faster enzymatic process is inhibited (Barbier-Baudry et al, 2003). The Sn(Oct) 2 catalyzed microwave assisted polymerization of ε-caprolactone ( -CL) can be initiated by methacrylic acid or acrylic acid yielding radical polymerizable PCL macromonomers.…”
Section: Poly(ε-caprolactone)mentioning
confidence: 99%
“…Loupy et al investigated the effect of microwave irradiation on the polymerization of ε ‐caprolactone with lanthanide halide catalysts using different heat profiles 51. When 200 W microwave power was applied constantly, broader molecular weight distributions were obtained compared to the use of an initial power boost (300 W).…”
Section: Ring‐opening Polymerizationsmentioning
confidence: 99%
“…Due to its multiple biomedical applications, the synthesis of PCL has received increased attention in the last years [ 9 , 10 ]. There are two methods for the preparation of biomedical PCLs: the polycondensation of 6-hydroxyhexanoic acid and the ring-opening polymerization (ROP) of ε-caprolactone (CL) [ 9 , 11 ]. The ROP process is more often used because of the higher molecular weight and lower polydispersity of the obtained polyesters [ 9 ].…”
Section: Introductionmentioning
confidence: 99%